The development of EPSAS: contributions from the literature - Caruana, J.; Dabbicco, G.; Jorge, S. M.; Jesus, M. (Accounting in Europe, 2019)
EPSAS are being considered in the EU context where a need for harmonisation in Governmental Accounting (GA) has been recognised as important to increase the reliability of sources of information to the National Accounts (NA) figures. However, GA and NA are two different and parallel reporting systems at national level, even if, within the European context, EPSAS intend to contribute for their convergence. The relationship between GA and NA has been recurrently addressed in the literature over the last two decades, with professionals being more proactive while academics have been more reactive in the debate. Several issues have been raised. This paper recaptures and revises these issues, synthesising academic and practitioner literature, archival documents and reports of EU working groups, from 1996 to 2018. The analysis highlights the more controversial areas, and those that seemed already settled but yet are now, within the context of EPSAS development, being raised again. Specifically, the paper calls attention to (1) the need to manage between two different conceptual frameworks of GA and NA; (2) the importance of interdisciplinary collaboration between the professionals involved, namely accountants, public administrators and statisticians; (3) the role of budgetary accounting and the alignment required between reporting in GA and NA, reducing and harmonising adjustments to be made when translating data from one into the other; and (4) the need to address auditing issues, as EPSAS on their own may not be enough to ensure reliability of the information reported.